All-inside meniscal repair devices and techniques. (March 2012) - Tuman, Jeff; Haro, Marc S; Foley, Sarah; Diduch, David
Techniques and devices for meniscal repair are evolving, including for all-inside meniscal repair. The first-generation all-inside meniscal repair devices were simplistic in design, but their technical difficulties and risks led to the development of second-generation devices. These devices employed the suture anchor concept for repair and confirmed the safety of use through standard anterior arthroscopic portals. Third-generation devices introduced the idea of rigid, bioabsorbable materials; unfortunately, these demonstrated higher failure and complication rates compared with other repair techniques. They were also limited in their ability to adjust compression and tension across the repair. Now, fourth-generation devices have been developed that are flexible, suture-based, and allow for variable compression and retensioning across the tear. Each device has its own specifications and technical nuances. With a comprehensive understanding of the current devices available, the industry and surgeons may continue in the development of safer, more successful, user-friendly and cost-effective all-inside devices.